2020
DOI: 10.12659/msm.922988
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Drug-eluting Beads versus Conventional Transarterial Chemoembolization for Treating Peculiar Anatomical Sites of Gastric Cancer Liver Metastasis

Abstract: Background This study aimed to assess the relative safety and short-term efficacy of drug-eluting bead transarterial chemoembolization (DEB-TACE) and conventional transarterial chemoembolization (c-TACE) for treating peculiar anatomical sites of gastric cancer liver metastasis. Material/Methods Of the 68 patients with gastric cancer liver metastases confirmed by imaging and pathology, 35 were treated with DEB-TACE and 33 with c-TACE. The DEB-TACE group comprised 26 male… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…CSM-TACE combined with 125 I brachytherapy presented a favorable treatment response and survival as well as a satisfactory safety profile among patients with liver metastases from NSCLC after radical surgery. Both CSM-TACE and 125 I brachytherapy have been viewed as effective therapies for liver metastases (10,(13)(14)(15). It has been reported that CR, ORR, and DCR are 14.3%, 78.6%, and 90.5%, respectively, at 6 months after CSM-TACE in patients with liver metastases (13).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…CSM-TACE combined with 125 I brachytherapy presented a favorable treatment response and survival as well as a satisfactory safety profile among patients with liver metastases from NSCLC after radical surgery. Both CSM-TACE and 125 I brachytherapy have been viewed as effective therapies for liver metastases (10,(13)(14)(15). It has been reported that CR, ORR, and DCR are 14.3%, 78.6%, and 90.5%, respectively, at 6 months after CSM-TACE in patients with liver metastases (13).…”
Section: Discussionmentioning
confidence: 99%
“…In the past years, conventional transarterial chemoembolization (cTACE) has been viewed as a crucial treatment for liver metastases, while its therapeutic effect remains unsatisfactory (8)(9)(10). Recently, drug-eluting bead (DEB)-TACE has drawn a lot of attention in liver metastases, among which DEB-TACE using CalliSpheres ® microspheres (the first self-developed DEB in China) exhibits satisfying efficacy and tolerable safety not only in primary liver cancer but also in liver metastases (10)(11)(12)(13). For instance, CalliSpheres ® microsphere (CSM)-TACE shows acceptable survival benefits and tolerable safety in colorectal cancer liver metastases (13).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study concluded that regorafenib combined with DEB-TACE is superior to regorafenib monotherapy when considering the response, progression-free survival (PFS), and OS [ 6 ]. DEB-TACE and c-TACE demonstrated safety, feasibility, and short-term efficacy in treating gastric cancer liver metastasis [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, cTACE provides good survival benefits and possesses a favorable safety profile in hepatocellular carcinoma (10); meanwhile, it has also been reported that cTACE elicits a favorable treatment response from lung cancer patients (11). Currently, drugeluting beads TACE (DEB-TACE) is being proposed to achieve superior survival benefits in several cancers compared with cTACE, among which CalliSpheres® Microspheres (CSM) (the first microsphere product independently developed in China) can sustainedly and steadily release antitumor drugs in the tumor at high concentrations with favorable embolization efficacy (13)(14)(15). Moreover, past studies have proposed that CSM-TACE is effective and safe in treating several cancers (15)(16)(17), while its efficacy and safety in HNC are unclear.…”
Section: Introductionmentioning
confidence: 99%